2020
DOI: 10.1186/s40738-020-00073-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of tubal infertility in a tertiary hospital in a low-resource setting: a case-control study

Abstract: Background: Infertility is the inability to sustain a pregnancy in a woman with regular (2-3 times per week) unprotected sexual intercourse for a period of 1 year. This is a major public health problem that remains underrecognised in Cameroon and most countries in sub-Saharan Africa. This study aimed at identifying the risk factors associated with tubal infertility in a tertiary hospital in Douala, Cameroon. Methods: We conducted a case-control study at the Obstetrics, Gynaecology and Radiology Departments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…Besides, the practice of voluntary induced abortion is illegal in Cameroon except for therapeutic abortions where the pregnancy could compromise or jeopardize maternal or foetal outcomes. This has led to increased complications from abortions performed by unqualified medical and non-medical staff thereby increasing the maternal morbidity from post-abortion infections (endometritis), uterine synechiae, infertility and death 12,51,52 .…”
Section: Factors Associated With Couple Infertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the practice of voluntary induced abortion is illegal in Cameroon except for therapeutic abortions where the pregnancy could compromise or jeopardize maternal or foetal outcomes. This has led to increased complications from abortions performed by unqualified medical and non-medical staff thereby increasing the maternal morbidity from post-abortion infections (endometritis), uterine synechiae, infertility and death 12,51,52 .…”
Section: Factors Associated With Couple Infertilitymentioning
confidence: 99%
“…More than 90% of male infertility results from low sperm count (oligospermia), poor sperm quality (teratozoospermia), or both. The factors associated with couple infertility are hypogonadotropic hypogonadism, hyperprolactinaemia, disorders of ciliary function, cystic fibrosis, infections, systemic diseases and lifestyle-related factors/diseases [10][11][12][13] . Premature ovarian insufficiency, polycystic ovary syndrome, endometriosis, uterine fibroids and endometrial polyps may play a role in female infertility 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following selection process is presented in FIGURE 1. Eleven studies were ultimately selected (Parazzini et al, 1996;Marshall et al, 1998;Bulletti et al, 1999;Faerstein et al, 2001;Wise et al, 2004 ;Wellons et al, 2008 ;Templeman et al, 2009 ;Johnson et al, 2012;Yasui et al, 2018 ;Karlsen et al, 2020;Egbe et al, 2020). Their main characteristics are presented in TABLE 2.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery or ultrasounds were the most common method of diagnosing fibroids (n = 7). In two studies, the diagnosis was self-reported (but validated) (Marshall et al, 1998;Yasui et al, 2018) and in two studies the methodology was not explained (Karlsen et al, 2020;Egbe et al, 2020). None of the studies excluded women with submucosal lesions but data according to fibroid location were reported in only one of them (Johnson et al, 2012).…”
Section: Resultsmentioning
confidence: 99%